The Influence of Personality Factors on Entrepreneurial Intention - Rohman, Isnanda Zainur; Miswanto, Miswanto (Universitas Muhammadiyah Yogyakarta, 2020)
The aim of this paper is to examine the influence of personality factors (internal locus of control, need for achievement, and self-efficacy) on students’ entrepreneurial intentions. The sample of this research was selected by using purposive sampling. The data were collected by survey using questionnaires. Respondents who filled the questionnaires were 200 university students, studying in Yogyakarta. The data were analyzed by using multiple regressions. The result showed that all of the personality factors in this study had positive effects on students’ entrepreneurial intentions. In this study, it was found that the most significant variable to influence entrepreneurial intention was self-efficacy. The implication of this research is that if the number of entrepreneurs wants to be boosted, more attention must be paid to the personality factors of people.